Pengaruh Pendidikan Entrepreneurship Terhadap Minat Berwirausaha Mahasiswa STIE IBMT Surabaya - Aditia Hairuddin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The standard of human workforce quality in Indonesia is expected to improve along with the increasing number of graduates from universities each year. However, the reality is that the unemployment rate in Indonesia remains high. One of the efforts to address this is by providing entrepreneurship education. Among the many institutions of higher education, STIE IBMT Surabaya is one educational institution that actively encourages its students to become exceptional entrepreneurs through entrepreneurship education. The aim of this research is to determine and analyze the influence of entrepreneurship education on the entrepreneurial interest of STIE IBMT Surabaya students. The method used is descriptive quantitative. Sampling was conducted using a non-probability sampling method, specifically purposive sampling, with a total of 90 respondents. The data analysis techniques used are descriptive analysis and simple linear regression analysis. Based on the results of the t-test, entrepreneurship education has a highly significant influence on entrepreneurial interest. This is evidenced by the t-value (13.503) being higher than the t-table value (1.66235) and a significance value of 0.000 > 0.05.